Internal Combustion Engine Technology and Applications of Biodiesel Fuel - Wang, Enhua (IntechOpen, 2021)
This book examines internal combustion engine technology and applications of biodiesel fuel. It includes seven chapters in two sections. The first section examines engine downsizing, fuel spray, and economic comparison. The second section deals with applications of biodiesel fuel in compression-ignition and spark-ignition engines. The information contained herein is useful for scientists and students looking to broaden their knowledge of internal combustion engine technologies and applications of biodiesel fuel.